Determinants of low‐quality warfarin anticoagulation in patients with mechanical prosthetic heart valves. The nationwide PLECTRUM study. (20th February 2020) - Pastori, Daniele; Lip, Gregory Y. H.; Poli, Daniela; Antonucci, Emilia; Rubino, Luca; Menichelli, Danilo; Saliola, Mirella; Violi, Francesco; Palareti, Gualtiero; Pignatelli, Pasquale
Summary: Quality of warfarin therapy in patients with a mechanical prosthetic heart valve (MPHV) has been barely investigated. We analysed determinants of low time in the therapeutic range (TiTR <60%) in 2111 patients with MPHVs from the nationwide PLECTRUM study by the Italian Federation of Anticoagulation Clinics. Overall, 48·5% of patients had a TiTR of < 60%. At logistic regression analysis, arterial hypertension (odds ratio [OR] 1·502, P < 0·001), diabetes (OR 1·732, P < 0·001), heart failure (OR 1·484, P = 0·004), mitral site (vs. aortic) (OR 1·399, P = 0·006), international normalised ratio (INR) ranges of 2·5–3·5 (OR 2·575, P < 0·001) and 3·0–4·0 (OR 8·215, P < 0·001) associated with TiTR < 60%. TiTR is substantially suboptimal in MPHV patients, particularly in higher INR ranges.